Cutting Force prediction model by FEA and RSM when machining Hastelloy C-2HS with 900 holder - K., Kadirgama; M. M., Noor (2008)
Finite Element (FEA) Method and Response Surface Method (RSM) are used to find the effect of milling parameters (cutting speed, feedrate and axial depth) on cutting force when milling Hastelloy C-22HS. Based on the variance analyses of both the first- and second-order RSM models, the most influential design variable is the feedrate. Optimised cutting force values are subsequently obtained from the model equations. FEA model shows the distribution of cutting force.